Educational Obstacles Facing Primary School Teachers in Iraq from their Point of View - Diaa Saleh Mahdi Al-Attar (Journal of Global Pharma Technology, 2018)
The aim of this study is to identify the real obstacles related to primary school teachers in Iraq, which impede the development of the educational process, especially with regard to the student, curriculum, school administration and school buildings. To achieve this, a questionnaire was designed as a main tool in this study, the study sample consisted of (120) teachers and teachers in the schools of Karbala governorate. To collect the data from the members of this sample, a questionnaire was used consisting of five main fields. The validity and consistency of this questionnaire were verified. The results of the study showed that the teachers' awareness of the importance of the teacher and overcoming the obstacles to the performance of the tasks of his profession. The results of the study also revealed the impact of these axes on the role of the teacher is uneven, and the study presented a number of suggestions and recommendations.Keywords: Educational obstacles, Facing primary and school teachers.